2010
DOI: 10.2495/etox100111
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulation combined treatments for remediation of diesel contaminated soil

Abstract: Bioremediation is an important technology for the restoration of oil polluted environments by indigenous or selected microorganisms. In general, the rate of biodegradation depends on the number and types of microorganisms, the nature and chemical structure of pollutants to be degraded and the environmental conditions. In this study we have evaluated the efficacy of the application of four different biostimulation treatments for the biodegradation of diesel contaminated soils. The treatments applied involved: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…By contrast, the amount of alkane degradation bacteria (ADB) and naphthalene degradation bacteria (NDB) increased. This indicated diesel contaminants harmful to UB, as described by Calvo et al [51].…”
Section: Profiling Of Functional Genes and Enzyme Activity During Biodegradationsupporting
confidence: 53%
“…By contrast, the amount of alkane degradation bacteria (ADB) and naphthalene degradation bacteria (NDB) increased. This indicated diesel contaminants harmful to UB, as described by Calvo et al [51].…”
Section: Profiling Of Functional Genes and Enzyme Activity During Biodegradationsupporting
confidence: 53%
“…[55]. Different studies also showed the efficacy of using biostimulation as a post-treatment after oxidation with Fenton's reagents for the treatment of hydrocarbons [56,57].…”
Section: Effect Of Biostimulationmentioning
confidence: 99%